Identification of Phytophthora colocasiae genes differentially expressed during infection on taro (Colocasia esculenta). (January 2015) - Nath, Vishnu Sukumari; Rajitha, Moochatil; Darveekaran, Sree Sankar; Hegde, Vinayaka Mahabaleswar; Jeeva, Muthulekshmi Lajapathy; Misra, Raj Shekar; Veena, Syamala Swayamvaran; John, Neetha Soma; Anjanadevi, Indira Parameswaran; Raj, Mithun
Abstract: Taro leaf blight caused by Phytophthora colocasiae presents the single biggest constraint for taro production globally. Understanding the molecular mechanisms underpinning infection will be of great asset in managing this devastating disease. Here, we used a suppression subtractive hybridization (SSH) approach to identify genes that are differentially expressed in P. colocasiae during a compatible interaction with taro. A cDNA library enriched for upregulated P. colocasiae genes were generated using a novel inoculation system that allowed the physical separation of the induced mycelium from the host. Reverse northern analysis of randomly selected clones revealed clear induction of these genes during infection. Sequence analysis of these genes classified them into various biological, molecular and cellular processes. Reverse transcriptase quantitative PCR (RT-qPCR) assay of selected P. colocasiae genes showed an increased expression of these genes during infection of taro. The results of the study provide valuable insights into the gene expression patterns in P. colocasiae during infection on taro, which could be important for pathogenicity. Graphical abstract: Highlights: The study reports for the first time, genes upregulated in Phytophthora colocasiae upon infection in taro. Several genes were differentially expressed in the early stage of infection, suggesting their role in pathogenicity. The study projects novel insights on the transcriptional reprogramming of P. colocasiae during infection.